-2z+3=-4z+11

Simple and best practice solution for -2z+3=-4z+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2z+3=-4z+11 equation:


Simplifying
-2z + 3 = -4z + 11

Reorder the terms:
3 + -2z = -4z + 11

Reorder the terms:
3 + -2z = 11 + -4z

Solving
3 + -2z = 11 + -4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '4z' to each side of the equation.
3 + -2z + 4z = 11 + -4z + 4z

Combine like terms: -2z + 4z = 2z
3 + 2z = 11 + -4z + 4z

Combine like terms: -4z + 4z = 0
3 + 2z = 11 + 0
3 + 2z = 11

Add '-3' to each side of the equation.
3 + -3 + 2z = 11 + -3

Combine like terms: 3 + -3 = 0
0 + 2z = 11 + -3
2z = 11 + -3

Combine like terms: 11 + -3 = 8
2z = 8

Divide each side by '2'.
z = 4

Simplifying
z = 4

See similar equations:

| 2n+-9=n+6 | | -2y+4=6y+4 | | 2(x-6)=5-(x+2)+4 | | P-(p+6)=5(p-3)+4p | | 27(1/3x-1/19)=10 | | b^2-4b-5=-5 | | 11/9=4/81 | | 15w+9=0.5w+96 | | X^2+8x+10=-5 | | 1/3x+12=2x-3 | | (7n+1)(n-6)=0 | | (4a-5)(5a-2)=o | | 3x/4-1/4=2 | | 24x^2-14-3=0 | | 0.5=0.4-0.25solve | | 27(x+5)=36x | | f=wpy | | 2b-8=6b+1 | | X-10=-x-4 | | -16=x-15 | | 1x+2x+1+-20= | | (x-3)/5=13 | | .8(y+3)=4.8 | | -5(t-4)-4(9-2t)=2(t-9)+8 | | 10+x+9=40 | | 9[4-9(7-8)]= | | 42m^2-29m-5=0 | | 20+x=-13 | | 2-T/3=T/6 | | 5k+2=3 | | 3(5n-1)^1/3-2 | | p/8-1=3 |

Equations solver categories